PEMANFAATAN KARBON AKTIF DARI LIMBAH SERAT SAGU (Metroxylon sagu) SEBAGAI ADSORBEN DALAM PEMBUATAN SMART FILTER LIMBAH CAIR DOMESTIK - Andyani; Suaedi; Nurasia (Cokroaminoto Journal of Chemical Science, 2020)
This study aims to make a Smart Filter for domestic liquid waste by utilizing activated carbon from Sago Fiber Waste as an adsorbent. The stages of this research consisted of making activated carbon, characterizing activated carbon and testing the smart filter. The results of the research show that activated carbon from sago fiber (Metroxylon sago) is needed to produce the best Smart Filter in reducing levels of domestic liquid waste (household liquid waste) by as much as 20 g. This is based on the results of tests carried out in this study where the more activated carbon is used, the more reduction in waste content is produced, resulting in a decrease in the content of Chemycal Oxygen Demand (COD) by 4%. The Smart Filter test results in reducing levels of domestic liquid waste (household liquid waste) in the Gray Water category gave a good effect according to the results obtained for all test parameters carried out, namely turbidity, pH and Chemycal Oxygen Demand (COD). Based on observations made from the use of Smart Filters with two forms, namely powder and granules, better results are obtained, namely the use of Smart Filters that use powdered activated carbon.